Approaching vertical greenery as public art: a review on potentials in urban Malaysia - Abu Bakar, Nur Izzah; Mansor, Mazlina; Harun, Nor Zalina (Department of Architecture, Faculty of Civil Engineering and Planning, Institute of Technology Sepuluh Nopember, 2013)
When landscape becomes the work of art, it is becoming more significant to the community. However, finding practical and effective ways in which public art could present an environmental cause is yet to be fully explored. Therefore, one way to approach this issue is by increasing the Vertical Greenery technology's application, especially at the wall of building in the city. Vertical Greenery (VG) varies in term of definition, but all in all, it can be interpreted as the growing of plants in, up, or against the facade of a building. On the other hand, public art can be referred as an artwork that is located in public space, which welcomes public interactions. Thus, in order to further study the potential of VG implementation as public art, this paper reviews 25 selected real life projects in urban Malaysia as reference studies, which include Kuala Lumpur, Selangor Johor and Penang that applied VG in their development. It explored whether the VG’s implemented is, for public art. Based on the study, the researcher found that VG is implemented for its environmental, economic and aesthetic value. The researcher also noted that all VG that has been implemented at the developments in some ways portray the basic idea of public art which is an artistic expression that is positioned in a freely accessed public space for the public to use, but not just any art placed outside yet still carries the basic concept of art, which to beautify spaces. Hence, the result had shown significant potentials for VG to be introduced as a new form of sustainable public art in urban Malaysia.